Mathematical Modeling of High-risk Behaviors in Reformation and Social Assistance Centers - Khademi, Nahid; Khoramdad, Malihe; Shakiba, Ebrahim; Barkhordar, Nasrin; Rostamian, Hassan; Saeidi, Shahram; Zangeneh, Alireza (International Journal of Engineering and Technology, 2018)
There is an increasing rate of high-risk behaviors in women, particularly those in prisons and high-risk places. This study was aimed to determine the high-risk behaviors among women residing in reformation and social assistance centers of Kermanshah province, Iran.In this cross sectional study, 480 women living in reformation and social assistance centers, central prisons, social welfare centers, suburban areas, high-risk neighborhoods and hangouts; were randomly selected. The primary data were collected via demographic and high-risk behavior questionnaire. To detect HIV infection, a rapid test was used as well as ELISA test in suspected cases. Statistical analysis was performed using Chi Square and Pearson Correlation Coefficient tests. The most prevalent high-risk behaviors in the subjects were addictive drug abuse (73.5%), arrest by judicial centers (59.2%), illegitimate sexual contacts (52.3%), and suicide (52.3%), respectively. The rapid HIV test revealed a positive correlation co-efficiency between HIV-positive individuals with crystal meth abuse (r=0.119, P=0.035).Associations were also observed between smoking and narcotic drug abusing (p
Keywords: High-risk behaviors; Women; Iran; AIDS